Analisis Determinan Faktor Struktur Modal Di Bursa Efek Indonesia Tahun 2016-2019 - Carissa Dessy Rianti; Marsheila Eka Dianti; Sandra Zaeni (Jurnal Syntax Transformation, 2022)
The purpose of this study is to analyze the influence of profitability, asset structure, company growth, company size on capital structure. For this purpose, the research object was conducted at oil palm plantation companies listed on the Indonesia Stock Exchange for the period 2016-2019. Based on the existing sample criteria obtained by 11 companies that meet the criteria, the company presents the complete financial statements of the research period. The research measurement tool used is multiple linear regression analysis because it has the ability to predict the influence of free variables on bound variables. The results of the study concluded that the variables of profitability, asset structure and growth of the company have an influence and significant on the structure of capital while the size variables of the company have no influence on the structure of capital. Simultaneously the four variables have a strong influence of 60.6% on the capital structure. The method used in this study is a method of multiple linear regression analysis that is research conducted to determine the influence of one or more variables on certain variables that are causation